Physical Adaptation of College Students in High-Altitude Training: Empirical Findings and Curriculum Development Insights to Support Sustainable Development Goals (SDGs) - Xing, Guoquan; Chano, Jiraporn; Thadanatthaphak, Yada; Wu, Chi Cheng (Bumi Publikasi Nusantara, 2025)
This study aimed to design an educational curriculum that enhances physical adaptation to high-altitude environments by integrating principles of sustainable development in physical education. Using a descriptive method, the research surveyed college students and professionals to assess current training practices in high-altitude settings. Results indicated limited effectiveness in explosive power, flexibility, and endurance due to environmental challenges and inadequate structural support. Because adaptation to hypoxic conditions requires targeted strategies, findings emphasize the need for altitude-specific flexibility training and psychological preparation. The curriculum development is grounded in educational frameworks and aligns with Sustainable Development Goals (SDGs) to support student well-being and resilience. This approach provides a scientific basis for improving physical readiness and promoting long-term health and equity in high-altitude education.